Uso de la tecnología en el aprendizaje virtual para los estudiantes del tercer año básica de la Unidad Educativa Teodoro Alvarado Garaicoa del cantón Alfredo Baquerizo Moreno, Jujan, provincia del Guayas - Jovanna de los Ángeles, Barzallo Piedra (2021)
The case study work entitled USE OF TECHNOLOGY IN VIRTUAL LEARNING FOR STUDENTS OF THE THIRD YEAR BASIC OF THE TEODORO ALVARADO GARAICOA EDUCATIONAL UNIT OF THE PARISH ALFREDO BAQUERIZO MORENO, CANTÓN JUJAN, PROVINCIA DEL GUAYAS, which was based on recognizing the importance of the use of technological media that are used more frequently today such as: cell phone, laptop, computers, television etc. to provide a good learning in the students who were chosen for this case. The current society in which we live where there have been very noticeable changes and that has changed part of our daily lives, such as the way we interact, communicate, work, shop, present ourselves and learning. But the change does not come only from the use of technical equipment, we can say with certainty that we are moving towards a technological society that seeks more flexible, level and efficient organizational forms; in this society, access to information and adequate knowledge is achieved through more open, accessible and democratic channels, let's consider schools as a space for technological innovation. In this study will be used in a series of techniques and methods of data collection, direct observation and basic monitoring to obtain results on the level of performance of students who were chosen as a sample, for the preparation of the report, based on the statistics of the data obtained, in order to draw the appropriate conclusions.